Metabolism of β-Methylaspartate by a Pseudomonad - Sebek, O. K. (1968)
A bacterium was isolated from soil which utilizes threo-β-methyl-l-aspartate, certain other amino acids, and a variety of organic substances as single energy sources. It is, or closely resembles, Pseudomonas putida biotype B. The ability of this organism to rapidly decompose such amino acids is dependent on inducible enzyme systems. Dialyzed cell-free extracts of this bacterium metabolize β-methylaspartate only when catalytic amounts of α-ketoglutarate, or pyruvate, and pyridoxal phosphate are also present. The main products formed from β-methylaspartate under these conditions are α-aminobutyrate, carbon dioxide, and α-ketobutyrate. When l-aspartate is substituted for β-methylaspartate in this system, it is converted mainly to alanine and carbon dioxide. β-Methyloxalacetate is decarboxylated, and the resulting α-ketobutyrate is converted enzymatically in the presence of glutamate to α-aminobutyrate which accumulates. The added keto acids are converted, in part, to the corresponding amino acids probably by transamination. The data indicate that β-methylaspartate is converted to α-aminobutyrate, and aspartate to alanine, by a circuitous transamination-β-decarboxylation-transamination sequence rather than by a direct β-decarboxylation.